2014
DOI: 10.1587/nolta.5.466
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of coupled Stirling engines

Abstract: Abstract:Because of an increasing demand on electric power and limited resources for conventional fuels, highly efficient engine that is capable of converting energy resource to electric power with a small loss is awaited. In this respect, Stirling engine provides a strong potential because of its efficient thermodynamic cycle, which is ideally close to the theoretical limit of the Carnot cycle. Practical use of the Stirling engine, however, has been limited because of its low output power. Towards its wider a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
5
1
Order By: Relevance
“…Compared to the power of P total = 161 W generated by the independent engines with their natural frequencies, the output energy was significantly increased to P total = 358 W in the synchronized state, indicating the increase of 186 %. Compared to the increase of 60 % achieved by the directly coupled Stirling engines in our previous study [2], the present result has been highly improved. This clearly demonstrates the significance of realizing the synchronized oscillations of the Stirling engines for the use of their population sum as the output energy.…”
Section: Experiments 2: Synchronization Of Two Stirling Engines Couplecontrasting
confidence: 59%
See 3 more Smart Citations
“…Compared to the power of P total = 161 W generated by the independent engines with their natural frequencies, the output energy was significantly increased to P total = 358 W in the synchronized state, indicating the increase of 186 %. Compared to the increase of 60 % achieved by the directly coupled Stirling engines in our previous study [2], the present result has been highly improved. This clearly demonstrates the significance of realizing the synchronized oscillations of the Stirling engines for the use of their population sum as the output energy.…”
Section: Experiments 2: Synchronization Of Two Stirling Engines Couplecontrasting
confidence: 59%
“…In the previous study [2], two Stirling engines were directly coupled to each other to realize their synchronization. It has been shown that the synchronized engines produced much higher electric power than that of the nonsynchronized engines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Theoretical studies of synchronization of the limit cycle and chaotic oscillators have been carried out for many years [1]. From the experimental side, synchronization phenomena are observed in various oscillators, e.g., Stirling engines [2], metronomes [3] and candles [4]. Synchronization phenomena rely on the assumption that the oscillators are coupled with each other.…”
Section: Introductionmentioning
confidence: 99%